2019
DOI: 10.1016/j.conbuildmat.2019.04.258
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness evolution of natural hydraulic lime mortars at early ages measured through EMM-ARM

Abstract: This paper focuses on the mechanical characterization of the early age behavior of three NHL mortars with different water/lime ratios. A vibration-based technique with continuous data recording (Elastic Modulus Measurement through Ambient Response Method -EMM-ARM) was used to measure stiffness of the different mortars that were found to range between 2.5 and 4.1 GPa on day 7. Other physical and mechanical properties such as strength and density were measured as a function of sample preparation protocols -vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The use of HL and NHL gave almost similar porosity, which was about 15% higher in the case of reference mortars and about 20% higher in the case of mortars with lava aggregate compared to values obtained for PCHL-R and PCHL-LA, respectively. Similar porosity values of NHL reference mortars were obtained recently, e.g., Garijo et al [80]. Accordingly, Pachta et al [81] received lime mortar with sand of siliceous origin porosity of 31%, which was in agreement with porosity value of control lime mortar.…”
Section: Resultssupporting
confidence: 86%
“…The use of HL and NHL gave almost similar porosity, which was about 15% higher in the case of reference mortars and about 20% higher in the case of mortars with lava aggregate compared to values obtained for PCHL-R and PCHL-LA, respectively. Similar porosity values of NHL reference mortars were obtained recently, e.g., Garijo et al [80]. Accordingly, Pachta et al [81] received lime mortar with sand of siliceous origin porosity of 31%, which was in agreement with porosity value of control lime mortar.…”
Section: Resultssupporting
confidence: 86%
“…This effect was found to be more significant for the wet specimens in comparison to the ambient-dry counterparts. It has already been shown that wet HNL mortar samples typically exhibit lower mechanical strengths than those in air-dry conditions [6,67]. In such cases, when the brick stiffness is higher than that of the mortar, the mortar is in a triaxial compression state, whilst the bricks are in axial compression and lateral tension.…”
Section: Comparative Findings and Resultsmentioning
confidence: 99%
“…Despite a slight difference of results was detected between the two sets of specimens (i.e. q and V were higher in mechanically compacted specimens compared to hand compacted ones, the contrary happened for f f and f c ), they were considered acceptable compared to the variation encountered in each of the individual tests, and also comparable with the variation encountered in the tests performed in experimental studies on aerial lime mortars [7,11,37]. Indeed, the percentage differences between the results obtained did not exceed 5% for the bulk density and the ultrasonic pulse velocity, and about 10% for the flexural and compressive strength.…”
Section: Repeatability Of Resultsmentioning
confidence: 89%
“…The figure also shows the comparison with the available data derived by literature concerning different types of mortar that can be possibly used in restoration. In particular, data related to cement-aerial lime blended mortars [45], natural hydraulic lime mortars [37] and cement-natural hydraulic lime blended mortars [49] were used for the comparison. Figure 12 also specifies the mix proportions for each mortar (Cement:Lime:Sand) and the water:binder ratio by volume.…”
Section: Integrative Discussion Of the Experimental Outcomes And Comparison With Literature Resultsmentioning
confidence: 99%
See 1 more Smart Citation